PENGARUH PERENCANAAN, PELAKSANAAN, LAPORAN KEUANGAN, EVALUASI DAN TUNJANGAN TERHADAP AKUNTABILITAS KINERJA DENGAN SISTEM INFORMASI SEBAGAI VARIABEL MODERASI PADA SEKRETARIAT BPSDM PERHUBUNGAN - Pandu Winara; Rossje Surya Putri (Universitas Methodist Indonesia, 2019)
This study aims to determine the effect of planning, implementation, financial statement, evaluation, and benefits on performance accountability with information systems as moderating variables at the BPSDM Transportation Secretariat. In accordance with the Instruction of the President of the Republic of Indonesia (Inpres) Number 7 of 1999 concerning Performance Accountability of Government Agencies, it requires every government agency as an organizing element of the state government to account for the implementation of basic tasks and functions as well as the authority to manage resources based on a strategic plan determined by each agency. The government referred to in the form of reports submitted to their respective superiors, supervisory institutions, and accountability assessors and finally submitted to the president as head of government. The population in this study were employees of the BPSDM Transportation Secretariat. The number of samples used in this study is assumed to be 100 respondents.